Global embodied rare earths flows and the outflow paths of China's embodied rare earths: Combining multi-regional input-output analysis with the complex network approach. (10th April 2019) - Wang, Xibo; Yao, Mingtao; Li, Jiashuo; Ge, Jianping; Wei, Wendong; Wu, Bin; Zhang, Mengying
Abstract: Both the direct and indirect need of rare earths (RE) are performing important functions in our daily life with their wide use in a range of products. However, previous studies have focused primarily on the direct use of RE and neglected the indirect effect, especially the indirect RE flow between economies. In this paper, we built an embodied rare earths flow network based on the global multi-regional input-output analysis framework and complex network theory, of which the community structure and small world nature are analyzed using complex network theory. We find that world embodied rare earths link network is clearly divided into 2 communities and the network can reveal the small world nature characteristics. Moreover, China, Germany and USA are the three most important economies based on the comprehensive analysis of the network's degree centrality, strength centrality, betweenness centrality and eigenvector centrality on the basis of network centrality theory. Furthermore, we analyze China's embodied RE outflow paths and the degree of dependence on embodied RE for each economy. Finally, some meaningful policy implications are provided.